2014
DOI: 10.4995/wrs.2014.1468
|View full text |Cite
|
Sign up to set email alerts
|

Population structure in Tunisian indigenous rabbit ascertained using molecular information

Abstract: Understanding the genetic structure of domestic species provides a window into the process of domestication. This study attempts to offer an insight into the prevailing genetic status of Tunisian indigenous rabbit breeds using molecular markers. Thirty-six microsatellite loci were used to provide a comprehensive insight into the genetic status and relationship among 12 Tunisian indigenous rabbit populations. A total of 264 rabbits from villages of the Tozeur and Kebili regions were studied. Standard statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
4
7
2
Order By: Relevance
“…Overall, the genetic distance between the three populations was small which suggested that the three populations were closely related and had a common ancestor. Comparing with the previous studies, the genetic distance between the three populations was lower than that reported for Tunisian rabbit populations [ 32 ].…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…Overall, the genetic distance between the three populations was small which suggested that the three populations were closely related and had a common ancestor. Comparing with the previous studies, the genetic distance between the three populations was lower than that reported for Tunisian rabbit populations [ 32 ].…”
Section: Resultscontrasting
confidence: 82%
“…[ 4 ], while it was closer to the values of Tunisian’s rabbits ( H o ranging from 0. 365 to 0.482) [ 32 ] and Spanish breeds ( H o ranging from 0.36 to 0.48) [ 31 ]. The variation between the results of this study and Abdel-Kafy et al .…”
Section: Resultsmentioning
confidence: 99%
“…The genetic differentiations among 4 NMER populations (K=4) were mainly discernible according to the geographic regions. This result disagrees with Ben Larabi et al (2014) in North Africa, who reported that differentiation among 12 local Tunisian rabbit populations could not be classified by geographic regions.…”
Section: Discussioncontrasting
confidence: 56%
“…5.50) was higher than that of indigenous rabbit breeds from Tunisia (on av. 3.30) (Ben Larbi et al, 2014) and lower than that of 7 domestic breeds (on av. 10.067) from China (Wu et al, 2010).…”
Section: Genetic Variation and Intra-population Diversitymentioning
confidence: 99%
“…0.568) were higher than those of domestic rabbit breeds from Tunisia (on av. 0.512) (Ben Larbi et al, 2014) and Egypt (0.525) (Grimal et al, 2012). The H O and H E per population ranged from 0.319 for the JPN to 0.548 for the ADIB and from 0.382 for the JPN to 0.622 for the ADIB.…”
Section: Genetic Variation and Intra-population Diversitymentioning
confidence: 99%